Evaluasi Sistem Surveilans Hipertensi dengan Pendekatan Atribut di Kota Semarang - Najla Salsabila Noor (Media Gizi Kesmas, 2023)
Background: Surveillance is the activity of systematic and continuous collection, processing, analysis, and dissemination of appropriate information to interested parties so that appropriate action can be taken. Hypertension surveillance experienced dynamic upward changes in 2019. Although experiencing dynamic changes, the number of cases is getting bigger. Thus, the increasing prevalence of hypertension makes hypertension surveillance so important. Objectives: To determine the results of the assessment of hypertension surveillance that has been carried out. Methods: The research approach was qualitative-evaluative research. The variables in this study are simplicity, flexibility, acceptance, sensitivity, positive predictive value, representativeness, timeliness, stability, and data quality. The research design was an evaluation of hypertension surveillance, and the data collection methods were observation and interview. Results: The data collected is limited to patients or sufferers who come to the community health center and from other agencies involved, not yet involving people with hypertension independently or individually; the data at the Puskesmas can be collected on time according to the deadline requested by the Semarang City Health Office; the hypertension surveillance system is still very simple; the fields in the hypertension surveillance system are also easily accepted by the agencies involved in data collection; the data have flexibility when related to changes in cost, energy, and time; and the hypertension surveillance system has stability based on the data collection mechanism itself. Conclusions: Semarang City's hypertension surveillance system still relies on an officer-based data collection mechanism and is not yet community-based (with hypertension patients, and Data collection can be timely using a simple form, and surveillance outcomes in all attributes are of good quality.